Cost metrics for effective Learning Objects reuse - Sampson, Demetrios; Zervas, P. (2011)
In the field of technology-enhanced learning, Learning Objects (LOs) are the key paradigm for developing and sharing digital educational content. The main advantage of LOs is considered to be their potential for component-based reuse in different learning settings supporting different learning activities. However, despite the importance of the concept of reuse and its potential benefits in digital educational content production and deployment, there are only limited efforts to study issues related to LOs the cost effectiveness LOs reuse. This is an obstacle for interested parties (such as people, organizations and initiatives) in assessing the conditions for and eventually implementing systematic LOs reuse. In previous work, a workflow for LOs reuse has been proposed that can support reuse of resources within the context of learning activities design and development. In this paper, we use this workflow to define metrics for cost effective LOs reuse and discuss the cost effectiveness conditions in various use cases. © 2011 IEEE.